Heterothermy as the Norm, Homeothermy as the Exception: Variable Torpor Patterns in the South American Marsupial Monito del Monte (Dromiciops gliroides) - Nespolo, Roberto F.; Mejías, Carlos; Espinoza, Angelo; Quintero-Galvis, Julián; Rezende, Enrico L.; Fontúrbel, Francisco E.; Bozinovic, Francisco (Frontiers in Physiology, 2021)
Hibernation (i.e., multiday torpor) is considered an adaptive strategy to face food shortages in seasonal environments. It has been considered functionally different from daily torpor, a physiological strategy to cope with unpredictable environments. However, recent studies have shown large variability in torpor patterns, especially in species from tropical and subtropical regions. The arboreal marsupial “monito del monte” (Dromiciops gliroides, Microbiotheriidae) is a relict component of the South American temperate rainforests, known to express both daily and multiday torpor under controlled laboratory conditions. Here we combined laboratory and field experiments to characterize torpor patterns in this marsupial on a broad thermal range. We used intraperitoneal data-loggers and simultaneous measurement of ambient and body temperatures (TA and TB, respectively) for predicting resting metabolic rate (RMR) applying Newton's cooling law. We also analyzed RMR in function of environmental variables (TA, natural photoperiod changes, food availability, and body mass changes) using mixed-effects generalized linear models. Our results suggest that: (1) animals experience torpor routinely, independently of TA and even during the reproductive period in the austral summer; (2) winter torpor also occur in D. gliroides, with a maximum bout duration of 5 days and a mean defended TB of 3.6  0.9 ºC (one individual controlled TB at 0.09ºC); (3) the best model explaining torpor occurrence (AIC weight = 0.59) discarded all predictor variables excepting photoperiod and the interaction between photoperiod and food availability. Altogether, these results confirm that this marsupial experience a dynamic form of torpor that is independent of TA. These data add to a growing body of evidence characterizing tropical and sub-tropical heterothermy as a form of opportunistic torpor, which contrasts against the more fixed seasonal heterothermic patterns found on Holarctic species. Being D. gliroides considered a basoendotherm, these results support the idea that early mammals depended mainly on passive thermoregulation for TB control.